Multi‐Objective Optimization of the Food‐Energy‐Water Nexus Problem: A Review of the Key Concepts and Emerging Opportunities in Objective Functions, Decision Variables, and Optimization Techniques - Isaac Okola; Elisha Opiyo Omulo; Daniel Orwa Ochieng; Gilbert Ouma (Earth's Future)
Abstract Food, energy, and water are basic needs that are quite important in livelihood sustainability. In most situations, their interactions make trade‐offs between these key areas of need challenging to attain. For the Food‐Energy‐Water Nexus (FEWN), there exists a need for appropriate decision‐making tools that may help to surmount such challenges. Multiobjective Optimization Approaches (MOAs) have emerged as potential solutions within this domain. The major components explored in this review include the objective functions, decision variables, and optimization techniques within MOAs. Despite their potential, few studies comprehensively address the key concepts of these components, the role of stakeholder involvement, the limitations of existing research, and the emerging technological opportunities that could enhance MOAs in the FEWN. The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses protocol, was combined with Meta‐ethnography to select, review, and analyze the literature. The data synthesis was done by meta‐ethnography, finding key terms to categorize objective functions, decision variables, and optimization techniques and developing key concepts related to MOAs in the FEWN. Key terms for categorizing objective functions are maximizing economic, environmental, and social benefits and food, energy, and water security. For the decision variables, the key terms include availability, accessibility, and sufficiency, while the optimization techniques are Mathematical Programming and Metaheuristics. Besides, emerging technologies create substantial opportunities to improve the performance of MOAs. Therefore, there is a need to develop MOAs that integrate economic, environmental, and social aspects to support the sustainability of the FEWN.